SENTING METER - Willy Atthoriq; Wimbrayardi Wimbrayardi; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2015)
Abstract Implementation of the work Senting Meter to serve as expression of the composer’s musical experience, music composition has inspired and encourage a composer to learn music. In the implementation of the work, the composer present a collabortive instrument rebana with modern instrument with new packaging, so the composer can show that the game is the rebana can be merged with other instruments and not just use a rebana it just as well as eliminate the thought of teens today that says the game is boring rebana. Here composer present a development techniques Senting (a stong blow) is also one of the techniques of the game rebana. the development of rhythm, sound and colour on the paper Senting Meter is rendered into other instruments, both in terms of musical studies as well as the selection of the instrument. So the works presented more attractive and can be accepted at this time. Keywords: Senting, Meter